2006
DOI: 10.1136/gut.2005.083113
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon alfa-2a (40KD) plus ribavirin in chronic hepatitis C patients who failed previous interferon therapy

Abstract: Background:The management of patients with chronic hepatitis C who have relapsed or failed to respond to interferon based therapies is an important issue facing hepatologists. Aims: We evaluated the efficacy and safety of peginterferon alfa-2a (40KD) plus ribavirin in this population by conducting a multicentre open label study. Patients: Data from adults with detectable serum hepatitis C virus (HCV) RNA who had not responded or had relapsed after previous conventional interferon or conventional interferon/rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 19 publications
(21 reference statements)
9
73
0
Order By: Relevance
“…Some authors showed that, after previous treatment with conventional IFN, with or without RBV, relapsers have significantly higher SVR when retreated with PEG-IFN alpha-2b and RBV than do nonresponders to previous treatment (55% vs. 20%; p<0.001) [9]. The same was observed by Sherman et al, who found that, after retreatment with PEG-IFN alpha-2a and RBV, the SVR rate was 23% in nonresponders and 41% in relapsers [12]. The results of the retreatment of true nonresponders to PEG-IFN and RBV obtained by the Brazilian researchers are better than those reported in international studies [10,11].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Some authors showed that, after previous treatment with conventional IFN, with or without RBV, relapsers have significantly higher SVR when retreated with PEG-IFN alpha-2b and RBV than do nonresponders to previous treatment (55% vs. 20%; p<0.001) [9]. The same was observed by Sherman et al, who found that, after retreatment with PEG-IFN alpha-2a and RBV, the SVR rate was 23% in nonresponders and 41% in relapsers [12]. The results of the retreatment of true nonresponders to PEG-IFN and RBV obtained by the Brazilian researchers are better than those reported in international studies [10,11].…”
supporting
confidence: 70%
“…Of the relapsers treated, 57% [10] and 62% [11] achieved an SVR. These SVR rates in relapsers are higher than, for example, the rates of 41% and 59% obtained, respectively, in Canada (by Sherman et al) and in France (by Moucari et al) [12,13]. In analyzing the response in relapsers by genotype, the Brazilian researchers found that an SVR was achieved in 69-70% of those infected with genotype 3, compared with 43-44% of those infected with genotype 1 [10,11].…”
mentioning
confidence: 76%
“…Of the remaining 42 full-text articles, 30 were excluded because they did not meet inclusion criteria, leaving 14 fulllength papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16] meeting criteria for inclusion in the meta-analysis. Finally, 6 abstracts identified by manual search [17][18][19][20][21][22], were also included, only for the evaluation of the publication bias.…”
Section: Selection Of Trialsmentioning
confidence: 99%
“…Several studies of retreatment with pegylated IFN (PEG-IFN) plus ribavirin in patients who failed to respond to the combination of pegylated and non-pegylated IFN plus ribavirin have been published [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The results of these studies are inconclusive or conflicting because of the relatively small samples and the differences in patient characteristics, study design combining relapsers and nonresponders, doses of IFN and ribavirin administered in the first course, and retreatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we believe that the addition of SMV to PegIFN/RBV may significantly improve the SVR. AEs in these included RCTs were clinically manageable and the most common AEs caused by the triple regimen were headache, fatigue, and influenza-like illness; all of which were well-known AEs associated with the dual regimen (28)(29)(30)(31)(32)(33)(34)35). Our meta-analysis showed that the pooled incidence of AEs with triple therapy was similar to that with the dual regimen, suggesting that addition of SMV to PegIFN/RBV at least did not exacerbate the AEs of the dual regimen.…”
Section: Discussionmentioning
confidence: 60%